PERBEDAAN ANGIOGENESIS PADA PULPA SETELAH APLIKASI EKSTRAK PROPOLIS DAN KALSIUM HIDROKSIDA - Camelia Ariesdyanata; Cecilia G.J. Lunardhi; Agus Subiwahjudi (Universitas Airlangga, 2019)
Background : Propolis is a resinous hive product collected by bees ( Apis Mellifera ) from tree buds and mixed with secreted bee wax in order to avoid bacterial contamination in the hive, and also to seal it. Propolis is employed for the treatment of various infectious diseases because it is wellknown that is has antibacterial and anti-inflammatory properties. Calcium hydroxide was introduced to the dental profession in 1921 and has been considered the “gold standard” for direct pulp capping materials in the past decades. Aims :This research is to investigate the development of new blood vessels ( angiogenesis ) in rat's dental pulp following application of propolis extract and calcium hydroxide. Methods : There was 43 Strain Wistar rats of 8–16 week old and 200–250 grams in weight were used in this study. The rats were randomly divided into 6 groups. Pulp exposures were performed on the occlusal surface of right maxillary first molars. At the 1st and 4th groups, as the control group, without pulp capping paste. At the 2rd and 5th groups, pulp exposure was applied with propolis extract. And at 3th and 6th groups pulp exposure was applied with calcium hydroxide ,and the 7th group is negative control is a normal teeth. Pulp exposure was applied with propolis extract. After that, all of the cavities were filled with light cured glass ionomer cement as a permanent filling. Animals on the 1st, 2rd, and 3th groups were decaputed after 7x24 hour post pulp capping material application and were sent for histological examination which new blood vessels ( angiogenesis ) cells were present. And at the 4th, 5th, 6th groups were culled after 7x 24 hour post pulp capping material application and were sent for histological examination which new blood vessels ( angiogenesis ) evaluated were present. Result : All sample were histopathological examinated and data was statiscally analysed using one way ANOVA the histological analysis revealed that the development of the new blood vessels occurred in all group. The new blood vessels ( angiogenesis ) of propolis extract group was milder compared to the control and calcium hydroxide group, with statistical analysis showed significant difference (p > 0.05). Conclusion: The development of new blood vessels is earlier happened in group capping material containing propolis and which show with reduce the amount of the new blood vessels in days 7 and 14 than the other group.